A Problematic Conflation of Justice and Equality: The Case for Equity in Music Therapy. Issue 2 (14th July 2020) - Leonard, Hakeem
Abstract: A historical basis and a therapeutic foundation are given for understanding the importance of equity when considering contexts of race in music therapy, specifically with African-American or Black clients. Those contexts are broad, including, but not limited to Black clients, Black music, diversity and inclusion, safe spaces, multiculturalism, access to music therapy education, access to services. Examples are given of the Black experience in the United States related to self-definition, self-sufficiency, growth, and resiliency. Both cultural and musical aesthetic contextualization are pointed to, and connections are drawn between the navigation of Black people through different types of oppressive systems, and the negotiation of double-bind dilemmas that try to force Black disembodiment when trying to live authentic personhood in the face of proscriptive and prescriptive forces. Despite this systemic oppression, Black people continue to show a resilience in society as well as therapeutic and health settings, which is seen more readily when therapists and professionals can center in the margins the lived experience of Black clients, decenter themselves where appropriate, and practice a critical consciousness that actively uses counterhegemonic and antiracist practices. As music therapists have begun to understand joining ethics and evidence together through the self-advocacy of some populations, we must do the same while explicitly centering equity in our work with Black clients. If music therapists truly espouse justice, then there should be a critical examination of this in the profession-- in ourselves, our work, our relationship to music, our organizations, and in our education and training.